Is There an Effect of Caffeine Intake, Physical Activity, and Internet Addiction on Headache Severity in University Students? - Demirer, Büşra; Güneş, Musa (International Journal of Mental Health & Addiction, 2025)
Headache is a widespread multifactorial pathology, especially in the university student. Understanding these factors is essential for understanding headaches' primary and secondary causes and applying the proper treatment. This cross-sectional study aimed to evaluate the effects of university students' (n = 657, F 527, M 120) caffeine intake, physical activity levels, and internet addictions (IA) on headache severity. The amount of caffeine intake of the participants, headache severity, IA with the Young Internet Addiction Test (YIAT), and physical activity levels were determined. A one-unit increase in the daily average caffeine intake of students is 1.21 times the risk of experiencing severe headache (OR 1.216, 95% Cl 1.447–1.022, p = 0.027), and an increase of 1 point in the YIAT score is 1.98 times the risk of experiencing severe headache (OR 1.983, 95% Cl 1.624–2.421, p < 0.001). No significant correlation was found between the physical activity MET scores of the individuals and the severity of headaches (p = 0.632). These results suggest that adding questions about dietary habits, caffeine intake, and IA in the anamnesis for headaches will be important for understanding the secondary causes.